INCIDENCE OF DASIOPS SP. (DIPTERA: LONCHAEIDAE) IN FLOWER BUDS OF PASSIFLORA LIGULARIS (MALPIGHIALES: PASSIFLORACEAE) AND SOME CLIMATIC FACTORS, OXAPAMPA, PERU - Orihuela, Conie (2022)
In Peru, Passiflora ligularis (Juss, 1805) (granadilla) is one of the passionflowers with the highest demand in the market. Diptera of the genus Dasiops (Lonchaeidae) are detrimental to the cultivation of passionflowers because the larvae feed on the internal structures of flower buds, flowers and fruits, causing between 50 and 60% losses in the production of said crops. This research aimed to determine the incidence of Dasiops sp. in flower buds of a granadilla crop and the climatological factors (temperature, precipitation and relative humidity) of the San Pedro de Grapanazú Farm (Huancabamba - Oxapampa, Pasco, Perú), during the dry season, between the months of September and October 2020. The experimental and exploratory protocol consisted of three fortnightly collections of 50 flower buds, which were dissected to determine the incidence of Dasiops sp.; in addition, 120 flower buds containing the larval stage were collected from which adults were obtained for the identification of the genus. At the same time, a daily monitoring of climatological factors was carried out, with which biweekly averages were calculated to determine the Pearson correlation between said averages and the incidence of Dasiops sp. The results presented an incidence of 15.3% and a significant correlation between the incidence of Dasiops sp. in flower buds and the relative humidity, while the incidence-temperature and incidence-precipitation correlations were not significant. Given this, it was possible to conclude that there is an inverse and significant relationship between the incidence of Dasiops sp. and the relative humidity.